Nutritional and Sensory Evaluation of Injera Prepared from tef and Eragrostis curvula (Schrad.) Nees. Flours with Sorghum Blends - Ghebrehiwot, Habteab M.; Shimelis, Hussein A.; Kirkman, Kevin P.; Laing, Mark D.; Mabhaudhi, Tafadzwanashe (Frontiers in Plant Science, 2016)
Injera is a fermented, sour bread consumed as a staple food in Eritrea and Ethiopia. The bread can be prepared from various cereals but tef [Eragrostis tef (Zucc.) Trotter] is the most preferred ingredient. This study assessed the acceptability of injera prepared using grains of a closely related but underutilized grass, Eragrostis curvula (Schrad.) Nees. The nutritive value of the grains was compared and the sensory attributes of injera made from flours of tef (control) and E. curvula, each combined with 0, 5, and 10% of sorghum flour, were assessed using a tasting panel. Nutrient analysis showed that E. curvula contains more than double the amount of crude protein found in tef. E. curvula also contains higher fat, dietary fiber and mineral nutrients than tef. Injera made of E. tef and E. curvula flours showed non-significant differences in taste, texture, appearance and overall acceptability. This suggest that E. curvula has the potential to serve as a novel source of gluten-free flour for human consumption. Agronomically viewed, growing E. curvula could be more advantageous for smallholder farmers on marginal lands because the species is a perennial that can produce a seed harvest twice a year, unlike tef, which is annual crop. It also tolerates acidic soils better than tef.